BCI-838, an orally active mGluR2/3 receptor antagonist pro-drug, rescues learning behavior deficits in the PS19 MAPTP301S mouse model of tauopathy. (16th February 2023) - Perez-Garcia, Georgina; Bicak, Mesude; Haure-Mirande, Jean-Vianney; Perez, Gissel M.; Otero-Pagan, Alena; Gama Sosa, Miguel A.; De Gasperi, Rita; Sano, Mary; Barlow, Carrolee; Gage, Fred H.; Readhead, Benjamin; Ehrlich, Michelle E.; et al.
Highlights: BCI-838 is an mGluR2/3 receptor antagonist pro-drug. BCI-838 rescued deficits in object recognition memory in PS19 tauopathy mice. Treatment was effective whether begun at 3 or 7 months of age. mGluR2/3 dependent mechanisms underlie the behavioral deficits in PS19 mice. Abstract: Tauopathies are a heterogeneous group of neurodegenerative disorders that are clinically and pathologically distinct from Alzheimer's disease (AD) having tau inclusions in neurons and/or glia as their most prominent neuropathological feature. BCI-838 (MGS00210) is a group II metabotropic glutamate receptor (mGluR2/3) antagonist pro-drug. Previously, we reported that orally administered BCI-838 improved learning behavior and reduced anxiety in Dutch ( APP E693Q ) transgenic mice, a model of the pathological accumulation of Aβ oligomers found in AD. Herein, we investigated effects of BCI-838 on PS19 male mice that express the tauopathy mutation MAPT P301S associated with human frontotemporal lobar degeneration (FTLD). These mice develop an aging-related tauopathy without amyloid accumulation. Mice were divided into three experimental groups: (1) non-transgenic wild type mice treated with vehicle, (2) PS19 mice treated with vehicle and (3) PS19 mice treated with 5 mg/kg BCI-838. Groups of 10–13 mice were utilized. Vehicle or BCI-838 was administered by oral gavage for 4 weeks. Behavioral testing consisting of a novel object recognition task was conducted after drug administration. Two studies were performed beginning treatment of mice at 3 or 7 months of age. One month of BCI-838 treatment rescued deficits in recognition memory in PS19 mice whether treatment was begun at 3 or 7 months of age. These studies extend the potential utility of BCI-838 to neurodegenerative conditions that have tauopathy as their underlying basis. They also suggest an mGluR2/3 dependent mechanism as a basis for the behavioral deficits in PS19 mice.